Forced-ferromagnetic state in a Tm2Fe17H5 single crystal. (17th May 2017) - Tereshina, E A; Kuz'min, M D; Skourski, Y; Doerr, M; Iwasieczko, W; Wosnitza, J; Tereshina, I S
Abstract: We report the attainment of the ferromagnetic state in an interstitially modified heavy rare-earth-iron intermetallic compound in an external magnetic field. The starting composition is RE2 Fe17, which is the RE–Fe binary richest in iron. We concentrate on the Tm–Fe compound, which is the most sensitive to magnetic field. The maximum possible amount of hydrogen (5 at.H/f.u.) is inserted into a Tm2 Fe17 single crystal. We demonstrate that in a magnetic field of 57 T Tm2 Fe17 H5 reaches the ferromagnetic state with an enviably high polarization of 2.25 T.